Synthesis of new quinoline derivaties containing chalcone side chain - Thuy, Le Thi; Toan, Dao Huy; Tien, Hoang Xuan; Vu, Tran Khac (Vietnam Journal of Chemistry, 2012)
Novel chalcone-based quinoline derivatives (7a-c) were synthesized via a two-step procedure. In the first step, the reaction of 4-aminoacetophenone with different aldehydes in ethanol in the presence of NaOMe/MeOH afforded the corresponding chalcones (6a-c) in moderate to good yields. In the second step, the chalcones (6a-c) were respectively reacted with 4,7-dichloroquinoline in ethanol to obtain novel quinoline derivatives (7a-c) in good to excellent yields. All synthesized compounds were structurally characterized by modern spectroscopic methods: IR, 1H and 13C NMR